Muslims and the Charlie Hebdo Saga. (1st January 2015) - ,
Abstract : Of recent, newspapers across Europe carry headlines portraying Muslim radicalism. This is true giving the complicity of Muslim youth in various violent attacks. The headlines resonate amidst the growing nationalism in Europe, deeply tainted and lanced with conservatism. The Charlie Hebdo attack equally reiterated the protracted debates on the extent to which Islam is compatible with Western ethos. The attack further brought to surface the issue of freedom of expression, an essential part of Western democracy. This raises questions such as: who determines and what constitutes the public sphere; what are the lines of distinctions between the private and public domains; should there be a level of shared respect between the majority and minority; are European Muslims an integral part of the mainstream European society; what factors shape the radicalization of European Muslim youth; does religion actually have huge space in their minds; and, how much does constructivism present and resolve the protracted debate between the European Muslim community and the host society. Radicalization of European Muslim youth is less of ideology, but more of socio-economic deprivation.